Regulations on notional interest deduction (NID) – summary of 5 years of their enforcement - Karolina Rutkowska-Barnaś (Prawo Budżetowe Państwa i Samorządu)
The article focuses on regulations which have been enforced for over five years. These regulations allow taxpayer to treat hypothetical interest related to the so-called internal financing as a tax deductible cost. This can be done by making additional contributions by shareholders, as well as by allocating the profit which has been generated to reserve or to supplementary capital. The article presents doubts which arise regarding the application of the abovementioned regulations and de lege ferenda conclusions regarding the inaccuracies identified. The text also includes an analysis of so-called small anti-abusive clause.